2012
DOI: 10.1140/epje/i2012-12131-9
|View full text |Cite
|
Sign up to set email alerts
|

Noise-activated dissociation of soft elastic contacts

Abstract: Adhesive forces are capable of deforming a soft elastic object when it comes in contact with a flat rigid substrate. The contact is in stable equilibrium if the total energy of the system arising from the elastic and surface forces exhibits a minimum at a zero or at a slightly negative load.However, as the system is continually unloaded, the energy barrier decreases and it eventually disappears, thus leading to a ballistic separation of the contact. While this type of contact splitting has received wide recogn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The use of external Gaussian noise alleviates the effect of the nonlinear solid friction (“noise lubricity”) and enhances the mobility retaining the resolution characteristics of the gel (Figure a). An earlier report suggests a similar subcritical detachment of a soft elastic body from a rigid contactor in the presence of mechanical noise that promotes diffusive exploration of different states in an energy landscape and selects the least action pathway …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The use of external Gaussian noise alleviates the effect of the nonlinear solid friction (“noise lubricity”) and enhances the mobility retaining the resolution characteristics of the gel (Figure a). An earlier report suggests a similar subcritical detachment of a soft elastic body from a rigid contactor in the presence of mechanical noise that promotes diffusive exploration of different states in an energy landscape and selects the least action pathway …”
Section: Resultsmentioning
confidence: 95%
“…An earlier report suggests a similar subcritical detachment of a soft elastic body from a rigid contactor in the presence of mechanical noise that promotes diffusive exploration of different states in an energy landscape and selects the least action pathway. 17 Modified Langevin Model. The noise used here is the time-dependent acceleration = t ( ) qV t md ( ) , experienced by each base pair unit (see the SI).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For the case of a 1-μm-diameter polystyrene particle adherent to glass ( E * = 2.5 GPa) with a rather low work of adhesion of 1 mJ·m –2 , U a is ∼58 k B T for the JKR model and ∼28 k B T for the DMT model (i.e., much higher than the thermal energy k B T that drives the stochastic position fluctuations of the particle). Thermal forcing adopted in our adhesion experiments differentiates our approach from the studies reported in ref and , where adherent spheres rolled under the influence of a constant external bias force and controlled mechanical noise. In these experiments, the contact area between the sphere and the supporting substrate moved, and the dynamics of the system was strongly affected by nonlinear, hysteretic forces with the character of dry friction .…”
Section: Experimental Methodsmentioning
confidence: 99%